2016
DOI: 10.1186/s12913-016-1415-5
|View full text |Cite
|
Sign up to set email alerts
|

The association between multimorbidity and hospitalization is modified by individual demographics and physician continuity of care: a retrospective cohort study

Abstract: BackgroundMultimorbidity poses a significant clinical challenge and has been linked to greater health services use, including hospitalization; however, we have little knowledge about the influence of contextual factors on outcomes in this population. Objectives: To describe the extent to which the association between multimorbidity and hospitalization is modified by age, gender, primary care practice model, or continuity of care (COC) among adults with at least one chronic condition.MethodsA retrospective coho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
127
1
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(144 citation statements)
references
References 26 publications
9
127
1
7
Order By: Relevance
“…Moreover, while the proportion of those with multimorbidity is generally higher at older ages, in some populations the absolute number of people affected by multimorbidity is greater among those under 65 years of age due to the age structure of the population. 85,86,87,88,89 Multimorbidity is not exclusive to older people, and appears to affect a much broader cross-section of the population. The data are taken from a systematic review of 39 observational studies across 12 HICs, and illustrate a well-established positive association between age and prevalence of multimorbidity.…”
Section: Descriptive Epidemiology: Prevalence and Incidencementioning
confidence: 99%
“…Moreover, while the proportion of those with multimorbidity is generally higher at older ages, in some populations the absolute number of people affected by multimorbidity is greater among those under 65 years of age due to the age structure of the population. 85,86,87,88,89 Multimorbidity is not exclusive to older people, and appears to affect a much broader cross-section of the population. The data are taken from a systematic review of 39 observational studies across 12 HICs, and illustrate a well-established positive association between age and prevalence of multimorbidity.…”
Section: Descriptive Epidemiology: Prevalence and Incidencementioning
confidence: 99%
“…Ontario's health administrative data have been shown to be both valid and reliable, 20 and have been used previously to estimate medical costs 21 and study patterns of health services use. 18,[21][22][23][24][25]…”
Section: Setting and Datamentioning
confidence: 99%
“…Previous studies have shown better outcomes for HF patients cared for by physicians familiar with them after hospital discharges or emergency department visits. Other studies have also demonstrated that continuity of physician care reduces hospitalizations, especially for patients with high comorbidity burdens . Thus, it seems reasonable to hypothesize that continuity of inpatient care would be associated with improved outcomes—however, we acknowledge that this is a hypothesis that requires testing in a prospective, controlled study.…”
Section: Discussionmentioning
confidence: 76%
“…Although we acknowledge this weakness, we used validated International Classification of Diseases codes and data definition algorithms to build comorbidity profiles and the outcomes we evaluated (all‐cause rehospitalizations, LOS, and in‐hospital mortality) are relevant in HF patients regardless of ejection fraction, etiology, or clinical status. Second, although outpatient visits, particularly with familiar physicians or access to specialized clinics after discharge, would reduce readmissions, we do not have any data on whether availability of these outpatient resources varied over time or whether outpatient physician visits were or were not with physicians associated with the original hospital. Third, we had no data on distance from patient home to nearest hospital nor socioeconomic factors, such as homelessness or access to motor vehicle, that may have influenced both health outcomes and choice of hospital.…”
Section: Discussionmentioning
confidence: 99%